Embracing Generative Artificial Intelligence in Clinical Research and Beyond - Henry P. Foote, MD; Chuan Hong, PhD; Mohd Anwar, PhD; Maria Borentain, MD; Kevin Bugin, PhD; Nancy Dreyer, PhD, MPH; Josh Fessel, MD, PhD; Nitender Goyal, MD; Morgan Hanger, MPP; Adrian F. Hernandez, MD; Christoph P. Hornik, MD, PhD, MPH; Jennifer G. Jackman, PhD, MBA; et al. (JACC: Advances)
To explore threats and opportunities and to chart a path for safely navigating the rapid changes that generative artificial intelligence (AI) will bring to clinical research, the Duke Clinical Research Institute convened a multidisciplinary think tank in January 2024. Leading experts from academia, industry, nonprofits, and government agencies highlighted the potential opportunities of generative AI in automation of documentation, strengthening of participant and community engagement, and improvement of trial accuracy and efficiency. Challenges include technical hurdles, ethical dilemmas, and regulatory uncertainties. Success is expected to require establishing rigorous data management and security protocols, fostering integrity and trust among stakeholders, and sharing information about the safety and effectiveness of AI applications. Meeting insights point towards a future where, through collaboration and transparency, generative AI will help to shorten the translational pipeline and increase the inclusivity and equitability of clinical research.